CuI-Catalyzed Ullmann-Type Coupling of Phenols and Thiophenols with 5-Substituted 1,2,3-Triiodobenzenes: Facile Synthesis of Mammary Carcinoma Inhibitor BTO-956 in One Step - Al-Zoubi, Raed M.; Altamimi, Reem M.; Al-Jammal, Walid K.; Shawakfeh, Khaled Q.; Al-Zoubi, Mazhar S.; Ferguson, Michael J.; Zarour, Ahmad; Yassin, Aksam; Al-Ansari, Abdulla (Synthesis, 2021)
A facile and unprecedented synthesis of 2,3-diiodinated or 2,6-diiodinated diaryl ether/thioether derivatives through regioselective Ullmann-type cross couplings of 5-substituted 1,2,3-triiodobenzenes and phenols/thiophenols is described. Remarkably, the coupling reactions are simply controlled by the type of nucleophiles and the nature of C5 substituent at 1,2,3-triiodoarenes providing the internal or terminal coupling products in high regioselectivity and good isolated yields. Noticeable steric and electronic effects were clearly observed on both 1,2,3-triiodoarenes and nucleophiles. The highest yields were isolated from a combination between either electron-poor 1,2,3-triiodoarenes and phenols or electron-rich 1,2,3-triiodoarenes and thiophenols. The optimized conditions were found to be suitable for several functional groups. Using this methodology, mammary carcinoma inhibitor BTO-956 is prepared in only one step with excellent regioselectivity and good isolated yield. This report discloses the first method to prepare 2,3-diiodinated and 2,6-diiodinated diaryl ethers/thioethers in one step that is efficient, regioselective, and general in scope. The products are truly remarkable precursors for other transformations.
Keywords: ortho-diiododiaryl ethers/thioethers; BTO-956; Ullmann-type coupling; substituent effect; catalyst